The Potential for Religious Tourism in the Panchakoshi Area of Dailekh - Oli, Lok Bahadur; Woli , Lokendra (Medha: A Multidisciplinary Journal, 2024)
Religious tourism has been gaining increasing attention as a potential contributor to the local economy. This study explores the potential for religious tourism in the Panchakoshi area of Dailekh district, Nepal. The study exploits mixed research design, including surveys, interviews, and focus groups, to examine the current situation of religious tourism in the area, identify its potential strengths and weaknesses, and explore strategies for promoting its growth. This study is based on primary data collected in 2024 using purposive sampling methods. A total no of 57 respondents were surveyed from three local municipalities in the Panchakoshi area, and priests and monks from the pilgrimage sites. Religious tourism preserves valuable natural, architectural, religious, and cultural heritages that are unknown to outside societies. The potential of inaccessible places is closely linked to dimensional social aspects such as art, culture, and architecture. The opportunities for associated residents through a rational combination of nature, human skills, and social capital, with an accumulation of several entices the visitors so that the rational management of the tourist sites, cultural heritages, and places of interest could foster pilgrimage tourism and contribute to state development. The findings suggest the significant potential as a religious tourism destination. However, the area faces inadequate infrastructure, limited marketing and promotion, and a lack of coordination among stakeholders. This includes investments in infrastructure, improved marketing and promotion, and greater collaboration among stakeholders. Overall, the study highlights the potential of religious tourism as a tool for promoting economic development and cultural preservation in the Panchakoshi area and beyond.